Association of HPC2/ELAC2 and RNASEL non-synonymous variants with prostate cancer risk in African American familial and sporadic cases - Robbins, Christiane M. (2008)
INTRODUCTION: The RNASEL and HPC2/ELAC2 genes have been implicated in hereditary prostate cancer. Further assessment of the role of these genes in sporadic prostate cancer in African American men is warranted. METHODS: Genotyping of HPC2/ELAC2 variants (S217L, A541T), along with RNASEL variants (R462Q and E541D) was completed in 155 African American sporadic and 88 familial prostate cancer cases, and 296 healthy male controls. Logistic regression analysis was performed and Odds Ratios (OR) were calculated, while correcting for both age and population stratification using admixture informative markers. RESULTS: The HPC2/ELAC2 217L allele was significantly associated with risk of prostate cancer when taking all cases into account (OR=1.6; 1.0–2.6; P=0.03). The RNASEL 541D allele was associated with a decrease in risk of prostate cancer in sporadic cases (OR=0.4; 0.2–0.8; P=0.01). We did not detect an association between prostate cancer risk and the RNASEL R462Q variant. Results from haplotype analyses of the two RNASEL variants revealed highly significant differences in haplotype allele frequencies between cases and controls suggesting a synergistic effect at the RNASEL locus. One haplotype in particular (462R-541D) is far more frequent in our control population and shows a strong protective effect against prostate cancer (OR=0.47, P=8.1×10(−9)). CONCLUSIONS: These results suggest that HPC2/ELAC2 and RNASEL may play a role, however minor, in prostate cancer risk among African American men.